Primary Motor Cortex Organization Is Altered in Persistent Patellofemoral Pain. Issue 11 (14th March 2017) - Te, Maxine; Baptista, Abrahão F.; Chipchase, Lucy S.; Schabrun, Siobhan M.
Abstract: Objective: Reorganization of the primary motor cortex (M1) may be a feature of persistent patellofemoral pain (PFP), but no studies have investigated M1 organization in this condition. Here we aimed to examine the organization of the M1 representation of the quadriceps muscles in people with PFP and healthy controls. Design: Using a cross-sectional design, the M1 representation of the rectus femoris, vastus lateralis, and vastus medialis was mapped using transcranial magnetic stimulation in 11 individuals with PFP and 11 controls. Measures of pain severity were also made. Results: Individuals with PFP had reduced map volumes ( P < 0.001) and an anterior shift in the M1 representation ( P = 0.03) across all three quadriceps muscles compared with controls. Greater overlap of the M1 representation ( P = 0.02) and a reduction in the number of discrete cortical peaks ( P = 0.009) across all three quadriceps muscles were also observed in individuals with PFP compared with controls. There was no relationship between altered M1 organization and pain in PFP. Conclusions: These findings provide evidence of altered M1 organization in individuals with PFP compared with healthy controls. Notably, no difference in M1 organization was observed for the medial and lateral heads of the quadriceps in PFP. These data have relevance for our understanding of the pathophysiology of PFP and for the design of future treatments that aim to target M1 in this condition.